IMPLEMENTASI METODE MULTI FACTOR EVALUATION PROCESS (MFEP) DALAM MEMBUAT KEPUTUSAN UNTUK MEMILIH ASURANSI KESEHATAN - Merry Agustina (Jurnal Ilmiah Matrik, 2019)
The answer that arises when you get the question of the one most valuable thing in life is the family, because the family is home and home. Discussions about families with a lot of needs are one of them is the blindness of health insurance or medical insurance. Having health insurance for all family members is something that can not be ignored anymore even said to be absolute. Providing the best health insurance is one of the dear forms of computer cases for families. This reason also requires that we do not misselect a health insurance product. The research implements a multi-factor method of Evalation Process (MFEC) in the process of determining the best insurance product from 5 alternative companies asuransi based on 7 criteria/factor. Criteria/factors including complete Asuransi facility, extensive insurance provider, premium, cashless, existing short condition, insurance combination and insurance company's credibility. The results of the study received one of the best health insurance products based on calculation results using MFEP method with a value of 8